PERENCANAAN JALAN LINGKAR UTARA KOTA WONOSARI, KABUPATEN GUNUNG KIDUL, PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Anggraini, Anindita Dwi; Siringoringo, Judi Agnes Alvionita; Narayudha, Moga; Supriyono, Supriyono (Jurnal Karya Teknik Sipil, 2014)
Economic development and growth in the City Wonosari relatively fast growing, giving rise to the high mobility of the impact on the increase in traffic flow, traffic volume and road network system. One effort to do that with the planned construction of the North Ring Road City Wonosari able to support the creation of a transportation system that is effective, efficient, provide smooth transport, and increasing the role and function of national roads which have an important role in the conduct of regional transport flows in the Province Central Java. From the analysis of the northern ring road planning Wonosari City in accordance with the volume of traffic survey determined the number of lanes is 2/2 UD. From the calculation of the northern ring road planning Wonosari City, at the intersection specified the use of rigid pavement while traffic along the ring road north of the City Wonosari using flexible pavements.